Organic material additions have stronger effects on humic substances and enzyme activities than soil types. (28th August 2022) - Jin, Shengai; Ma, Hongbin; Jia, Long; Liu, Xinwei; Hussain, Qaiser; Song, Xiangyun; Cui, Liqiang; Wang, Chengji; Cui, Dejie
Abstract: The incorporation of organic materials derived from plant biomass into various soils is an effective strategy for increasing soil organic carbon (SOC). The comparative effect of organic material forms and soil types on carbon (C) sequestration has received little attention. On a C equivalent basis, wheat straw, wheat straw‐biochar, tobacco straw, and tobacco straw‐biochar were added to different soil types such as acidic, saline, and calcareous and incubated for 180 days. The structural characteristics of SOC, humic substance (HS) contents, and enzyme activities were investigated, and it was discovered that the C content of crop straws and biochar was primarily fixed in the form of humin (HU) in all soil types. Furthermore, biochar application did not increase humic acid (HA), whereas crop straws treatments did. Between HU and SOC, there was a significant positive correlation. SOC Aryl C was increased by biochar treatments, whereas phenolic C and O‐alkyl C were increased by straw treatments. Aromatic C correlated positively with SOC concentration, whereas polyphenol oxidase activity correlated positively with O‐alkyl C. The activity of polyphenol oxidase influenced the ormation of O‐alkyl C significantly. The majority of SOC functional groups and enzyme activities were found to have significant relationships with HS contents ( p value <0.05). These findings suggest that both soil types and organic materials influence HS and functional groups of SOC, with organic materials having a stronger influence on microbial activity than soil types. Biochar can be used for a wide range of soils to not only store more recalcitrant C but also make SOC more hydrophobic.